2015
DOI: 10.1177/1049732315570136
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Evaluating a Sociotechnical Intervention With Socially Isolated Older Adults

Abstract: The purpose of this article is to consider how ethical principles can inform the effective design and implementation of technology-based interventions that aim to promote the well-being of socially isolated older adults. We evaluated a new iPad application with small groups of older adults. In this article, we reflect on the ethical issues encountered at each stage of the research process. Drawing on the ethical principles of beneficence, research merit and integrity, justice, and respect, we identify key issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
0
31
0
2
Order By: Relevance
“…This can have positive consequences in the participants' unreserved feedback, but also lead to expectations of researchers becoming intimately involved in the social lives of participants. In addition, introducing new technologies into participants' lives provides an extra layer of complexity that can make it difficult to know how much researchers should intervene [15].The case studies collected during the CHI 2015 workshop further illustrate a need to continue our analysis of the ethical implications of such situations and how practitioners can (and when they should) maintain boundaries around the research.…”
Section: Building Rapport and Blurring Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…This can have positive consequences in the participants' unreserved feedback, but also lead to expectations of researchers becoming intimately involved in the social lives of participants. In addition, introducing new technologies into participants' lives provides an extra layer of complexity that can make it difficult to know how much researchers should intervene [15].The case studies collected during the CHI 2015 workshop further illustrate a need to continue our analysis of the ethical implications of such situations and how practitioners can (and when they should) maintain boundaries around the research.…”
Section: Building Rapport and Blurring Boundariesmentioning
confidence: 99%
“…In the previous workshop, McNaney and Vines [6] described the anxiety their participants experienced when the technology they were evaluating did not work as expected. In another example, older adults using an iPad app to share messages found that it sometimes exacerbated, rather than ameliorated, their loneliness when people did not immediately respond to their messages [15].…”
Section: Exposure To Risk and Harms Through New Technologymentioning
confidence: 99%
“…evaluations of interactive technologies with military or law enforcement partners [13]), or in care settings where participants are clients recruited through a care provider [25]. In other cases, participants might be compelled to participate because of perceptions about…”
Section: Consent and Participationmentioning
confidence: 99%
“…At CHI 2015 we held the inaugural workshop on "Ethical Encounters in HCI: Research in Sensitive Settings" [25]. This followed other recent workshops that focused on designing for and with vulnerable populations [21], enabling empathy in design research [17], and ethics in participatory design, held at CSCW 2015 [2].…”
Section: Summary Of Previous Workhops On Ethical Encounters In Hcimentioning
confidence: 99%
See 1 more Smart Citation